Adherence to Mediterranean diet, high-sensitive C-reactive protein, and severity of coronary artery disease: Contemporary data from the INTERCATH cohort. (August 2018) - Waldeyer, Christoph; Brunner, Fabian J.; Braetz, Julian; Ruebsamen, Nicole; Zyriax, Birgit-Christiane; Blaum, Christopher; Kroeger, Friederike; Kohsiack, Rebecca; Schrage, Benedikt; Sinning, Christoph; Becher, Peter M.; Karakas, Mahir; et al.
Abstract: Background and aims: Guidelines recommend a healthy diet as a cornerstone of cardiovascular disease (CVD) prevention. Although the Mediterranean diet (MD) is the best studied dietary pattern for CV outcomes, data on association between MD and severity of CAD are limited. Therefore, we analysed dietary data in association with the SYNTAX score in coronary artery disease (CAD) patients from the INTERCATH study. Methods: The INTERCATH study is an observational study in patients undergoing coronary angiography at the University Heart Center Hamburg. Coronary morphology is assessed by the SYNTAX score. A lifestyle questionnaire collects dietary data with food frequency questions at baseline. Based on seven dietary characteristics, we calculated an established Mediterranean diet score (MDS) with a range of 0–28 points at which 28 points reflect maximal adherence to MD. To investigate the association of MD with severity of CAD, we performed logistic regression analysis after adjustment for confounding factors. Results: Of 1121 patients, 27% were women. The median age was 70.7 years (interquartile range (IQR) 61.1, 77.0). CV risk factors were distributed as expected for a CAD cohort (31.3% diabetes, 81.1% arterial hypertension, 34.0% smoking, median BMI 26.6 kg/m 2 (IQR 24.1, 30.3), median LDL-C 87 mg/dL (IQR 65.0, 116, 6). Of all variables included, the strongest correlation with MDS was found for log (hs-CRP) (r = −0.21, p  < 0.001). Adherence to MD represented by a higher MDS was significantly associated with a reduced probability for a medium/high risk SYNTAX score of ≥23 with an odds ratio (OR) of 0.923 per point increase of MDS (95% confidence interval 0.869–0.979; p  = 0.0079). This association remained significant after adjustment for cardiovascular risk factors (OR 0.934, 95% CI 0.877–0.995, p  = 0.035). After further adjustment for log (hs-CRP), the association remained no longer significant (OR 0.955 (0.893–1.022, p  = 0.19). Conclusions: In this contemporary data set, we found an independent association of adherence to MD with a less complex CAD. Hs-CRP correlated significantly with adherence to MD and may be a marker of the vasoprotective effects of MD. These results strengthen the evidence for the protective effect of an MD pattern in CVD prevention. Highlights: The guidelines strongly recommend a healthy diet as a cornerstone of cardiovascular disease prevention. An association with Mediterranean diet (MD) has been shown for different vascular beds. There are no multivariate data regarding Mediterranean diet and the extent of coronary artery disease (CAD). The present study demonstrates an independent association between adherence to MD and the severity of CAD. hs-CRP showed the strongest correlation with adherence to MD and seems to be a marker of its vasoprotective effects.